A REVIEW ON INSTANT WHITE COFFEE AND INSTANT DECAFFEINATED COFFEE PROCESSING - Rahmi, Alia (Agroscientiae)
ABSTRACTÂ Instant white coffee is commonly associated with its preceding popular counterpart, the instant decaffeinatedcoffee. Questions of whether the two products are made from different variety of coffee bean, underwentdifferent processing techniques, or shares different caffeine contents, are poorly explained. The purpose ofthis review is to provide a better understanding on both products. Instant white coffee and instantdecaffeinated (black) coffee are made from similar coffee varieties, the Arabica and the Robusta. Bothproducts undergo similar coffee processing from harvesting, de-pulping, mucilaginous coating removal todrying. The difference takes place in the decaffeination process and the roasting process. Consequently, asinstant products, both are processed through an instant making process. Instant decaffeinated coffee isprocessed through a decaffeination process whereas it is not common for instant white coffee. Instant whitecoffee is processed through a lower roasting temperature and a shorter roasting time, hence possesses adetracted bitter aftertaste, a lightened colour, a higher caffeine content and a high acidic note. Instantdecaffeinated (black) coffee is processed at a higher roasting level (160 â 280oC; 20 â 40 minutes), thereforebears bitter aftertaste, dark colour, lower caffeine content and slightly acidic. The claim for health benefits,although not specifically on lean body mass, in white coffee, it is maybe true due to the high caffeine,chlorogenic and cafeic acid content. However, the claim for softness on the stomach is still debatable. Keywords: coffee, white coffee, decaffeinated coffee, instant